2015
DOI: 10.1001/jama.2015.9260
|View full text |Cite|
|
Sign up to set email alerts
|

Racial Bias in Health Care and Health

Abstract: A landmark report from the Institute of Medicine (IOM) in 2003 documented that from the simplest to the most technologically advanced diagnostic and therapeutic interventions, African American (or black) individuals and those in other minority groups receive fewer procedures and poorer-quality medical care than white individuals. 1 These differences existed even after statistical adjustment for variations in health insurance, stage and severity of disease, income or education, comorbid disease, and the type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(142 citation statements)
references
References 11 publications
1
141
0
Order By: Relevance
“…Yet, these populations have the poorest outcomes from common, chronic illnesses such as CKD, and are least likely to benefit from diagnostic and therapeutic advances [71, 72]. Translational genomic research also should take into account real-world primary care operations, and the need for real-time, point-of-care integration of test results with the EHR using CDS tools [7375].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these populations have the poorest outcomes from common, chronic illnesses such as CKD, and are least likely to benefit from diagnostic and therapeutic advances [71, 72]. Translational genomic research also should take into account real-world primary care operations, and the need for real-time, point-of-care integration of test results with the EHR using CDS tools [7375].…”
Section: Discussionmentioning
confidence: 99%
“…A 2003 Institute of Medicine (IOM) report showed that African Americans receive fewer procedures and lesser-quality medical care than caucasian Americans; this remained true even after adjusting for income, level of education, comorbid disease, and the type of care facility. 22,23 What's more, the quality of care and communication deficits between providers and people with SCD are even more marked than those between providers and African American patients, in a way that cannot be accounted for solely by age, race, education, or health status. 24 Improving relationships between health care providers in the medical system and patients with SCD may improve the trust that SCD patients have in medical professionals, which in turn may improve the overall quality of care among this underserved patient population.…”
Section: Disease Experiencementioning
confidence: 99%
“…31 (3) Higher levels of implicit bias among clinicians have been directly linked with inequities in treatment recommendations for African Americans and have been associated with poor quality of patientphysician communication. 23 (4) As a result, there can be a vicious cycle, as true or perceived discrimination from health care providers is associated with greater nonadherence to management regimens, 25 which is especially problematic for the nearly 30% of adults with SCD who report chronic pain. 2 Beyond pain, SCD is a complex condition that affects not only the patient's relationship with health care providers, but also their relationship with family and community.…”
Section: Disease Experiencementioning
confidence: 99%
“…Finally and more generally, evaluating the pathogenesis of a disorder among a highrisk population using molecular and epidemiological methods is a valuable approach to gaining new insights into disease pathogenesis. [46][47][48][49] In this article, we describe the methods of a large-scale, NIH-funded, longitudinal study evaluating the incidence and pathogenesis of chronic pain and neuropsychological outcomes among African-Americans experiencing MVC.…”
Section: Introductionmentioning
confidence: 99%